3D micro-porous conducting carbon beehive by single step polymer carbonization for high performance supercapacitors: the magic of in situ porogen formation - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy & Environmental Science, 2014)
We report non-templated synthesis of interconnected microporous carbon (IMPC) sheets having beehive morphology by direct pyrolysis of poly(acrylamide-co-acrylic acid) potassium salt in inert atmosphere without any activation. The presence of the alkali metal in the selected polymer precursor results in a high specific surface area of 1327 m(2) g(-1). Importantly, 80% of the pore volume is contributed by micropores with pore size ranging from 1-2 nm which is ideal for use as an electrode for supercapacitors. Whereas the rest of the surface area was contributed by a small fraction of mesopores and macropores due to the interconnected structure. The presence of three different types of pores make the material ideal for supercapacitor electrodes. IMPC was tested as an electrode in both aqueous and non-aqueous supercapacitors. All the aqueous measurements were done in 1 M H2SO4 solution with a potential window 1 V. A specific capacitance of 258 F g(-1) was realized at a constant charge-discharge current of 0.5 A g(-1) and it maintained at a value of 150 F g(-1) at 30 A g(-1). A long cycle stability of 90% capacitance retention was observed after 5000 charge-discharge cycles at a current density of 2 A g(-1). At the highest power density 13 600 W kg(-1) the energy density was found to be 3.1 W h kg(-1). Non aqueous performance was tested in the presence of 1 M LiPF6 in ethylene carbonate-di-methyl carbonate with 5 mg active material loading. A specific capacitance of 138 F g(-1) was obtained at a current density of 0.25 A g(-1) and it retained at a value of 100 F g-1 at 10 A g(-1). The material can deliver an energy density of 31 W h kg(-1) at its highest power density of 11 000 W kg(-1) in a two electrode system based on active material loading.

Enhanced capacitance retention in a supercapacitor made of carbon from sugarcane bagasse by hydrothermal pretreatment - Wahid, Malik; Puthusseri, Dhanya; Phase, Deodatta; Ogale, Satishchandra (Energy & Fuels, 2014)
A unique morphology-controlling protocol involving hydrothermal preprocessing before pyrolysis is presented to convert cellulosic waste in the form of sugarcane bagasse into three-dimensional (3D) interconnected, conducting, and high surface area carbon nanochannels. The large buffer spaces in such a porous carbon sample yield impressive electrochemical capacitance (C-sp) of 280 F/g at a current density of 1 A/g (and 275 F/g at 5 mV/s), with 72% retention even at a very high current density of 20 A/g. In contrast, the non-hydrothermally treated sample exhibits a C-sp value of 180 F/g at 1 A/g and only 52% retention at 20 A/g. The much better performance of the hydrothermally preprocessed bagasse-derived carbon (BHAC) can be ascribed to the solvent retention inside the buffer spaces created, negating the diffusional limitations of pore inaccessibility at higher scan rates. The BHAC has a high surface area of 1260 m(2)/g with a fairly good (11 wt %) concentration of oxygen functionality. The material renders a good energy density of Wh/kg at a power density of 3.5 kW/kg and shows good cyclability of 90% after 1000 charge/discharge cycles.

From waste paper basket to solid state and Li-HEC ultracapacitor electrodes: a value added journey for shredded office paper - Puthusseri, Dhanya; Aravindan, Vanchiappan; Anothumakkool, Bihag; Kurungot, Sreekumar; Madhavi, Srinivasan; Ogale, Satishchandra (Small, 2014)
Hydrothermal processing followed by controlled pyrolysis of used white office paper (a globally collectable shredded paper waste) are performed to obtain high surface area carbon with hierarchical pore size distribution. The BET specific surface area of such carbon is 2341 m 2 g(-1). The interconnected macroporous structure along with the concurrent presence of mesopores and micropores makes the material ideal for ultracapacitor application. Such waste paper derived carbon (WPC) shows remarkable performance in all solid-state supercapacitor fabricated with ionic liquid-polymer gel electrolyte. At room temperature, the material exhibits a power density of 19 000 W kg(-1) with an energy capability of 31 Wh kg(-1). The Li-ion electrochemical capacitor constructed using WPC as cathode also shows an excellent energy storage capacity of 61 Wh kg(-1)

Improving the energy density of Li-ion capacitors using polymer-derived porous carbons as cathode - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Electrochimica Acta, 2014)
High energy density Li-ion hybrid electrochemical capacitors (Li-HEC) are fabricated with 3 D architectured high surface area porous carbon (HSPC) derived from the poly(acrylamide-co-acrylic acid) potassium salt in a single step without any activating agent. The obtained HSPC exhibits high specific surface area of 1490 m(2) g(-1) and characterized with several analytical techniques. Li-HEC is fabricated with insertion type Li4Ti5O12 anode by adjusting the mass balance based on the single electrode performance with Li. The Li-HEC delivered the maximum energy density of similar to 55 Wh kg(-1), which is much higher than commercially available activated carbon (similar to 36 Wh kg(-1)). Further HSPC based Li-HEC delivered excellent cycleability and rendered similar to 87% of initial value after 2000 cycles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: energy density; Li-ion hybrid electrochemical capacitors; non-aqueous; porous carbon

MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.

Synthesis of an efficient heteroatom-doped carbon electro-catalyst for oxygen reduction reaction by pyrolysis of protein-rich pulse flour cooked with SiO2 nanoparticles - Gokhale, Rohan; Unni, SreeKuttan M.; Puthusseri, Dhanya; Kurungot, Sreekumar; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Development of a highly durable, fuel-tolerant, metal-free electro-catalyst for oxygen reduction reaction (ORR) is essential for robust and cost-effective Anion Exchange Membrane Fuel Cells (AEMFCs). Herein, we report the development of a nitrogen-doped (N-doped) hierarchically porous carbon-based efficient ORR electrocatalyst from protein-rich pulses. The process involves 3D silica nanoparticle templating of the pulse flour(s) followed by their double pyrolysis. The detailed experiments are performed on gram flour (derived from chickpeas) without any in situ/ex situ addition of dopants. The N-doped porous carbon thus generated shows remarkable electrocatalytic activity towards ORR in the alkaline medium. The oxygen reduction on this material follows the desired 4-electron transfer mechanism involving the direct reduction pathway. Additionally, the synthesized carbon catalyst also exhibits good electrochemical stability and fuel tolerance. The results are also obtained and compared with the case of soybean flour having higher nitrogen content to highlight the significance of different parameters in the ORR catalyst performance.

High surface area porous carbon for ultracapacitor application by pyrolysis of polystyrene containing pendant carboxylic acid groups prepared via click chemistry - Chhatre, Shraddha; Aravindan, Vanchiappan; Puthusseri, Dhanya; Banerjee, Abhik; Madhavi, Srinivasan; Wadgaonkar, Prakash P.; Ogale, Satishchandra B. (Materials Today Communications, 2015)

3D interconnected porous graphene sheets loaded with cobalt oxide nanoparticles for lithium-ion battery anodes - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy Technology, 2016)
Nanomaterials with high surface-to-volume ratio and tunable electronic and optical properties have expanded their use in variety of applications, especially energy conversion and storage. Here we report on the synthesis of a cobalt oxide (Co3O4)/3D-interconnected porous graphene (PG) nanocomposite by using a simple solvothermal route and its application as a Li-ion battery anode. Among the different compositions investigated, the composite PG-600 (with 50% PG) showed a discharge capacity of 700mAhg(-1) at a current density of 500mAg(-1) and maintained 90% retention after 80cycles. The high surface area of the 3DPG sheets helps the Co3O4 nanoparticles to form a uniform dispersion on the surfaces. The increased surface area (accessibility) and electrical conductivity of the composite result in significant enhancement in the capacity, cycling stability, and rate capability than the native Co3O4 phase.
Keywords: Cobalt oxide; Energy storage; graphene; lithium-ion batteries; Nanocomposites

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells

High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.